The railways of England North Western. Midland. Great Northern. Manchester, Sheffield, and Lincoln. North Eastern. South Western. Great Western. Great Eastern. Brighton and South Coast. Chatham and Dover. South Eastern - Acworth, W. M. 1850-1925 (John Murray, 1890)
This title deals only with railways terminating in London, and seeks to highlight the positive aspects of each line described, rather than concentrating on defects.
Includes index.
Keywords: Railroads -- England -- History.; elektronické knihy; electronic books